Assembleias fitoplanctônicas em uma praia estuarina amazônica (Chapéu Virado, Belém, PA): Variações nictemerais - REIS, Luciana Thaila Lopes (2019)
The coastal environment contains diverse biological communities associated with complex trophic webs. Phytoplankton constitutes the base of the trophic chain, playing an essential ecological role in aquatic ecosystems. The phytoplankton community variability is influenced by environmental factors and biological interactions. The present study was developed to access the composition and behavior of the phytoplankton and to evaluate the small-scale temporal variability in a fixed station at Chapeu Virado beach in Mosqueiro (Belém - Pará), during nictemeral cycles in consecutive years (2009/2010). The region is characterized by dynamic tide and oligohaline pattern. A 20-cm diameter cylindrical-conical shaped plankton net, 20 μm mesh, was towed on 100 meters-surface. Abiotic parameters (pH, salinity, temperature) were measured in situ. A Palmer-Maloney chamber was used for algae counting as many replicas as necessary to reach at least 400 individuals of the most abundant species. Identification was done under optical microscopy (OLYMPUS CX41) and with specialized references. Shannon-Wiener ecological indexes of diversity and Pielou evenness, Relative abundance, frequency of occurrence were calculated for the phytoplankton assemblage.. Variations in the abiotic parameters: pH (6.3 to 7), temperature (26 ℃ to 30 ℃) and salinity (0.22 to 4.5) were small between periods. The microphytoplaktonic community of Chapéu Virado beach was represented by 80 taxa, predominantly Bacillariophyta, followed by Charophyta, Chlorophyta and Cyanophyta. The most abundant taxon in December 2009 was Coscinodiscus sp and in November 2010 Polymyxus coronalis L.W. Bailey 1862. The average density of microphytoplankton ranged from 18.49 org L⁻¹ to 1.13 org L⁻¹. The highest richness values (39) were recorded in December 2009 at lowtide during daytime and the lowest in November 2010, during daytime ebb tide (17). Diversity varied from high to medium with a record of 3.3 bits per individual in the daytime daytime (November 2010) to 0.47 bits per individual (December 2009). The local microphytoplankton assemblage was strongly influenced by the daily cycle.